Relasi Patriarki dalam Keluarga Pada Novel Mudzakkirat Thabibah Karya Nawal el Saadawi - Suri, Nursukma; Fauziah, Fauziah; Lubis, Andi Pratama; Hutahaean, Paujiah (Arabi : Journal of Arabic Studies, 2024)
This study aims to determine how patriarchal relations in the family are in the novel/ Mudzakkirat Thabibah / ‘Memoirs of a Woman Doctor'. Patriarchal culture in the family carries the relationship between men and women regarding the division of roles in family and household life between men and women in the novel.. The method used is the descriptive analysis method. The results of the study indicate that patriarchal family relations in the novel relate to women's roles in household chores, the division of domestic roles, the father's role in education, learning manners and politeness, protection over children, reproductive education, and hair-cutting customs. The conclusion drawn from this study is that the patriarchal culture portrayed in the novel reflects the social reality of Egyptian society, reinforcing male dominance and its influential role in societal life.